2011
DOI: 10.1111/j.1399-5618.2011.00932.x
|View full text |Cite
|
Sign up to set email alerts
|

The burden of obesity among adults with bipolar disorder in the United States

Abstract: Objectives Previous studies of clinical samples of adults with bipolar disorder (BD) suggest that there is increased prevalence of obesity and that obesity is associated with greater BD severity. We therefore examined this topic in a representative epidemiologic sample. Methods The 2001–2002 National Epidemiologic Survey on Alcohol and Related Conditions was used to determine whether the prevalence of obesity is elevated among subjects with lifetime BD, and whether obesity is associated with greater severity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
4
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(98 citation statements)
references
References 55 publications
6
87
4
1
Order By: Relevance
“…In a large, nationally representative sample, Goldstein et al (2011) found a nearly two-fold age-, race-, and sexadjusted increased risk of obesity among adults with bipolar disorder versus controls. Obese participants with bipolar disorder also had greater comorbidity with anxiety disorders, longer depressive episodes, and significantly poorer physical and mental health functioning compared to non-obese people with bipolar disorder.…”
Section: Is There An Association Between Obesity and Psychiatry Disormentioning
confidence: 99%
“…In a large, nationally representative sample, Goldstein et al (2011) found a nearly two-fold age-, race-, and sexadjusted increased risk of obesity among adults with bipolar disorder versus controls. Obese participants with bipolar disorder also had greater comorbidity with anxiety disorders, longer depressive episodes, and significantly poorer physical and mental health functioning compared to non-obese people with bipolar disorder.…”
Section: Is There An Association Between Obesity and Psychiatry Disormentioning
confidence: 99%
“…[3][4][5] Increased rates of obesity, 6,7 diabetes, 8 hypertension, 9 dyslipidemia, 10 and metabolic syndrome [11][12][13] have been reported in recent clinical and epidemiological studies. 14,15 In addition to being exposed to the weight gain effects of the pharmacological treatment, BD patients are more likely to have sedentary lifestyles and poor dietary habits, 16 which are well-established cardiovascular risk factors. 17 Most of the abovementioned data come from developed countries, which have somewhat distinct realities from the developing world.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Elevated body mass index (BMI) is associated with hypertension, diabetes, certain types of cancer and cardiovascular disease (CVD). [7][8][9] The latter is particularly concerning because CVD is excessively prevalent and occurs prematurely in individuals with BD, 4,10 recently leading the American Heart Association to position BD as an illness that predisposes youth to premature CVD and atherosclerosis. 11 In addition to its adverse physical health correlates, obesity has been associated with a more pernicious course of BD in adults, including increased frequency of mood episodes, increased treatment resistance, poor cognitive function and increased suicidality.…”
Section: Introductionmentioning
confidence: 99%